PENGARUH BRAND IMAGE, KUALITAS PRODUK, DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN PRODUK BATIK DI DANAR HADI SURAKARTA - Siregar, Johan Samuel; Widiastuti, Erni (Universitas Of Surakarta, 2019)
In this study the authors have a goal to determine the effect of brand image, product quality, and price to the purchase decision of batik products in Batik Danar Hadi Surakarta either partially or simultaneously. Hypothesis in this research are: Suspected brand image, product quality, and price have a significant effect to purchasing decision of batik product in Batik Danar Hadi Surakarta either partially or simultaneously. Data needed in this research is primary data obtained by questionnaire method from sample counted 100 responden. Data analysis used in this research is multiple linear regression test, t test, F test and coefficient of determination test. The results of data analysis in this study can be concluded that the brand image, product quality, and price significantly influence the purchase decision of batik products in Batik Danar Hadi Surakarta either partially or simultaneously.